The Necessity to Seal the Re-Entry Tears of Aortic Dissection After TEVAR: A Hemodynamic Indicator - Li, Zhenfeng; Xu, Huanming; Armour, Chlöe Harriet; Guo, Yuze; Xiong, Jiang; Xu, Xiaoyun; Chen, Duanduan (Frontiers in Bioengineering and Biotechnology, 2022)
Thoracic endovascular aortic repair (TEVAR) is a common treatment for Stanford type B aortic dissection (TBAD). However, re-entry tears might be found distal to the stented region which transports blood between the true and false lumens. Sealing the re-entry tears, especially for the thoracic tears, could further reduce blood perfusion to the false lumen; however, it might also bring risks by re-intervention or surgery. Wise determination of the necessity to seal the re-entry tears is needed. In this study, patient-specific models of TBAD were reconstructed, and the modified models were established by virtually excluding the thoracic re-entries. Computational hemodynamics was investigated, and the variation of the functional index and first balance position (FBP) of the luminal pressure difference, due to the sealing of the re-entries, was reported. The results showed that the direction of the net flow through the unstented thoracic re-entries varied among cases. Excluding the re-entries with the net flow toward the false lumen may induce the FBP moving distally and the relative particle residence time increasing in the false lumen. This study preliminarily demonstrated that the hemodynamic status of the re-entry tears might serve as an indicator to the necessity of sealing. By quantifying the through-tear flow exchange and shift of FBP, one can predict the hemodynamic benefit by sealing the thoracic re-entries and thus wisely determine the necessity of further interventional management.